Opportunistic Invasive Infection by Group A Streptococcus During Anti–Interleukin-6 Immunotherapy. (18th August 2020) - Wilde, Shyra; Olivares, Katherine L; Nizet, Victor; Hoffman, Hal M; Radhakrishna, Suhas; LaRock, Christopher N
Abstract: Invasive group A Streptococcus (GAS) in immunocompetent individuals is largely linked to hypervirulent strains. Congenital immunodeficiencies and those acquired from chronic disease or immunosuppressant drugs also increase risk of severe illness. We recovered GAS from the blood of a patient receiving a biologic inhibitor of interleukin 6 (IL-6). Growth of this serotype M4 isolate in human blood or a murine bacteremia model was promoted by interleukin 1 or IL-6 inhibition. Hyperinvasive M1T1 GAS was unaffected by IL-6 in both models. These findings based on a natural experiment introduce IL-6 signaling deficiencies as a risk factor for invasive GAS. Abstract : In immunocompetent individuals, invasive infection by group A Streptococcus infection is linked to hypervirulent strains. We report that IL-6 immunosuppression can enhance the pathogenesis of lower virulence strains but not hypervirulent M1T1 clones, indicating that host and pathogen factors interplay in risk.